Astrocytes: GABAceptive and GABAergic Cells in the Brain - Liu, Jianhui; Feng, Xuanran; Wang, Yi; Xia, Xiaohuan; Zheng, Jialin C. (Frontiers in Cellular Neuroscience, 2022)
Astrocytes, the most abundant type of glial cells in the brain, play an important role in preserving normal neural functions and mediating the pathogenesis of neurological disorders. Recent studies have shown that astrocytes are GABAceptive and GABAergic. Astrocytes express GABAA receptors, GABAB receptors, and GABA transporter proteins to capture and internalize GABA. GABAceptive astrocytes thus influences both inhibitory and excitatory neurotransmission by controlling the levels of extracellular GABA. Furthermore, astrocytes synthesize and release GABA to directly regulate the brain function. In this review, we will highlight the recent progression supporting astrocytes as GABAceptive and GABAergic cells that act as an inhibitory node in the intercellular communication in the brain. Besides, we discuss the future directions for further expand our knowledge on the GABAceptive and GABAergic astrocyte signaling.